Temperature Measurement and Light Intensity Monitoring in Mini Greenhouses for Microgreen Plants Using the Tsukamoto Fuzzy Logic Method - Dea Suryaningsih; Riky Dwi Puriyanto (Universitas Ahmad Dahlan, 2023)
Microgreens are tender young plants that can be harvested as seeds and are a type of vegetable that can be harvested in about 7-14 days. Microgreen growth is influenced by several factors, including ambient temperature and light intensity. Microgreen plants require temperatures between 24°C – 30°C at all times during growth. These microgreen plants were grown on cocopeat growing media and given in a special room called a mini greenhouse with a size of 60 × 50 cm. The research method used is Tsukamoto's Fuzzy Logic. This research aims to make a tool to detect the temperature in a mini greenhouse. The research method used is Tsukamoto's Fuzzy Logic. Increasing temperature stability to keep the temperature in the mini greenhouse room at the ideal temperature. In this study, the sensors used were DHT 11 and grow light lamps. The results of this study indicate that the temperature and light intensity in this mini greenhouse are very stable and are at a temperature of 24°C-30°C with the accuracy of the sensor in this tool showing an error value of 5.39%.